2012
DOI: 10.1143/jjap.51.02ba03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anisotropic Strain Relaxation in Strained Silicon-on-Insulator Nanostructure by Oil-Immersion Raman Spectroscopy

Abstract: Precise stress measurements have been desired in order to apply strained Si substrates to next-generation transistors. Oil-immersion Raman spectroscopy enables the evaluation of the anisotropic stress state in the strained Si layer of the strained Si substrate even under (001)-oriented Si backscattering geometry. First, we found that the phonon deformation potentials (PDPs) reported by Anastassakis et al. in 1990 was the most valid among the three sets of PDP previous reported. Using these PDPs, the precise Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…As a result, the peak positions of the LO and TO phonon modes were −5.76 and −4.24 cm −1 , respectively. The biaxial stresses σ xx and σ yy were calculated using the following equation: centercenterΔitalicωnormalTOcenterΔitalicωnormalLO=centercenter2.88center0.54center2.30center2.30centercenteritalicσitalicxxcenteritalicσitalicyy,where Δ ω TO and Δ ω LO are the wavenumber shifts of the TO and LO phonon modes, respectively, from the Raman shift of stress‐free Si. The calculated stress values were σ xx = 1.23 GPa and σ yy = 1.27 GPa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the peak positions of the LO and TO phonon modes were −5.76 and −4.24 cm −1 , respectively. The biaxial stresses σ xx and σ yy were calculated using the following equation: centercenterΔitalicωnormalTOcenterΔitalicωnormalLO=centercenter2.88center0.54center2.30center2.30centercenteritalicσitalicxxcenteritalicσitalicyy,where Δ ω TO and Δ ω LO are the wavenumber shifts of the TO and LO phonon modes, respectively, from the Raman shift of stress‐free Si. The calculated stress values were σ xx = 1.23 GPa and σ yy = 1.27 GPa.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we clarified that both longitudinal optical (LO) and transverse optical (TO) phonon modes can be excited by SERS in the (001)‐oriented Si backscattering configuration . Excitation of the LO and TO phonon modes allows the evaluation of complicated stress states in Si and SiGe …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the forbidden optical phonon modes, the TO phonon modes, were excited even under the (001) Si backscattering geometry, using a high-numerical aperture (NA) liquid-immersion lens [22][23][24]. If all of the three optical phonon modes are detectable, the unknown three components of a stress tensor in Si can be obtained in theory [25][26][27][28][29][30][31][32][33][34][35]. The high-NA liquid-immersion Raman spectroscopy has great potential for measuring the complicated stress states in Si with high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the compliance tensor elements and phonon deformation potentials are material constants, but it has been pointed out before that their continued validity down to nm sizes is doubtful . Therefore, it is concluded that in order to achieve quantitative stress measurements in these structures, additional investigation will be required, for example, through simultaneous LO and TO phonon excitation using a high‐NA oil‐immersion objective for anisotropic stress measurements, and cross‐validation and calibration of the material constants with additional metrology (Nano‐Beam Diffraction, X‐ray Diffraction,...).…”
Section: Applications Of Nanofocused Raman Spectroscopymentioning
confidence: 99%